PENGARUH BIMBINGAN KELOMPOK DENGAN TEKNIK MIND MAPPING TERHADAP KEDISIPLINAN PENGGUNAAN GADGET DI SMA ANGKASA 2 JAKARTA - Hijrah Andriani Khatulistiwa; Thrisia Febrianti; Salohot Batubara (Prodi Bimbingan dan Konseling Fakultas Keguruan dan Ilmu Pendidikan | Universitas Islam As-Syafi'iyah, 2019)
This study aims to determine the effect of group guidance with mind mapping techniques on the discipline of using gadgets in SMA Angkasa 2 Jakarta. The population in this study were 108 students and a sample of 18 students were determined by simple random sampling. This research is a quantitative study with the method used is Quasi Experiment type Pretest-Posttest Control Group Design. Analysis of the data used is the T-Test with the help of SPSS 22.0 for Windows. The results showed that the discipline of using gadgets in the experimental group increased as evidenced by the paired sample t test with an error level of 5%, then the tcount> ttable (3,390> 2,306) which means that H0 was rejected and Ha was accepted. In the control group differed greatly from the experimental group as evidenced in the paired sample test t test with an error level of 5%, then the tcount> ttable (-0.403 <2,306) which means that H0 was accepted and Ha was rejected.